Factors influencing the impact of elephants on woody vegetation in private protected areas in South Africa's lowveld - Gadd, Michelle (My University, 1997)
This study of the impact of elephants, Loxodonta africana (Blumenbach), in private reserves ln South Africa's lowveld region aimed to determine the sizes and species of woody plants most often affected by elephants and the proportion and severity of elephant impact on the marula tree Sclerocarya birrea. The study was conducted in three parts: vegetation quadrats in areas where elephants had been foraging, direct observation of the feeding behaviour of hand-raised elephants, and transects to sample S. birrea across the study areas. To distinguish preferences, the frequency of elephant impact on each species was compared with the frequency with which it was encountered by the elephants. In the vegetation quadrats, I found that uprooting and leaf stripping were infrequent in all sizes of stems, Main stem breakage affected stems lese than 30 cm in diameter whereas branch breakage and bark stripping increased with increasing size. Favoured species were Combretum collinum, Acacia gerrardii, Albizia harveyl sclerocarya birrea, Dalbergia metenoxyton, and Pterocarpus rotundifolius. Notable among neglected species were Acacia toriifis, Tettnmelle prunioides, and Terminalia sericea which are favoured food items for elephants elsewhere. Other common species which were not selected by elephants were Acacia exuvielis, Cassine transvaalensis, Ehretia emoene, Euclea netalensis and Securinega virosa. Behavioural observation revealed that hand-raised elephants favoured eating Sclerocarya birrea, Combretum epiculeium, and Acacla nigrescens. The elephants stripped bark from A. nigrescens and S. birrea. Assessment of rnarula trees revealed that elephant impact killed fewer than 2% of stems during the preceding season. Fewer than 24% of trees had current season breakage or bark removal. Main stem breakage Was found in stems smaller than 40 ern in diameter. Ring barking was concentrated on the larger size classes, while the smaller size classes escaped any detectable form of elephant impact.
A Dissertation Submitted to the Faculty of SCience University of the Witwatersrand. Johannesburg for the Degree of Master of Science
Keywords: ELEPHANTS--SOUTH AFRICA--LOWVELD.; ANIMAL-PLANT RELATIONSHIPS--SOUTH AFRICA--LOWVELD.; ELEPHANTS--ECOLOGY.